EFFECT OF ULTRASOUND TECHNOLOGY ON WASTEWATER TREATMENT EMPHASIZING ON HEALTH ISSUE - Nasser Mehrdadi; Farshad Golbabaei Kootenaei (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Wastewater and sludge have huge pathogenic substances. So far, various physical and chemical processes have been used for disinfection, including chlorination, ozone and ultraviolet radiation. The use of this type of disinfectants is currently decreasing due to the hazards that they pose such as byproducts of disinfection, including carcinogenic Trihalomethanes. Nowadays, researchers have begun to use other processes that create less risks such as ultrasound technology. Ultrasoundwaves by breaking the cell wall causes reducing pathogenic populations and eliminating the risk of disinfection byproducts and are one of the newest methods for disinfection in water and wastewater treatment plants. For physical, chemical and biological effects of ultrasound waves on plants, ultrasound radiation results in the rotational movement of the protoplasm in individual cells and affects the growth rate of plants. In humans, the hypothesis is that exposure to ultrasound causes subsequent electrolytic balance changes in the nerve tissue and increases blood glucose levels. Ultrasound waves cause bacterial colony damage and thinning of the cell wall and the release of the cytoplasmic membrane. Mechanical effects of ultrasound waves can be used for water and wastewater disinfection. Methods: This research is a descriptive-analytic study that was carried out in a batch experiment. The goal of this research is to investigate the effect of ultrasonic waves on disinfection in South Tehran wastewater treatment plant. Results: The results showed that by increasing the time and density of the ultrasound, the rate of removal of E.coli increased. Also, the optimal sonification time was 30 minutes and the optimal ultrasound density was 2.5 watts per milliliter at a frequency of 20 kHz. E.coli removal rate in these conditions was more than 99%. Conclusion: According to the results of this study, the use of ultrasound waves has a significant effect on the elimination capacity of Escherichia coli and can be used as an appropriate alternative for stabilization and disinfection in wastewater treatment plants. Keywords: Ultrasound, Health, Wastewater, Treatment, Cavitation